2010
DOI: 10.1088/2041-8205/724/2/l207
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Gamma-Ray Emission From the Low-Mass X-Ray Binary System First J102347.6+003841

Abstract: The low-mass X-ray binary (LMXB) system FIRST J102347.6+003841 hosts a newly born millisecond pulsar (MSP) PSR J1023+0038 that was revealed as the first and only known rotation-powered MSP in a quiescent LMXB. While the system is shown to have an accretion disk before 2002, it remains unclear how the accretion disk has been removed in order to reveal the radio pulsation in 2007. In this Letter, we report the discovery of γ-rays spatially consistent with FIRST J102347.6+003841, at a significance of 7 standard d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…(msec) in subsequent Parkes observations. Nonetheless, the association with the Fermi-LAT source favoured XSS J1227 as a msec pulsar (MSP) binary (Hill et al 2011), similar to the first discovered rotational-powered MSP in a quiescent LMXB PSR J1023+0038 (Tam et al 2010). The number of MSP binaries detected in gamma-rays by Fermi-LAT has rapidly increased in the last year with the newly discovered systems PSR J1231-1411, PSR J0614-3329, and PSR J2214+3000 (Ransom et al 2011), PSR J1816+4510 (Kaplan et al 2012), PSR J0101-6422, PSR J1514-4946, and PSR J1902-5105 (Kerr et al 2012).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…(msec) in subsequent Parkes observations. Nonetheless, the association with the Fermi-LAT source favoured XSS J1227 as a msec pulsar (MSP) binary (Hill et al 2011), similar to the first discovered rotational-powered MSP in a quiescent LMXB PSR J1023+0038 (Tam et al 2010). The number of MSP binaries detected in gamma-rays by Fermi-LAT has rapidly increased in the last year with the newly discovered systems PSR J1231-1411, PSR J0614-3329, and PSR J2214+3000 (Ransom et al 2011), PSR J1816+4510 (Kaplan et al 2012), PSR J0101-6422, PSR J1514-4946, and PSR J1902-5105 (Kerr et al 2012).…”
Section: Introductionmentioning
confidence: 77%
“…Analogies to the MSP binary PSR J1023+0038 (Tam et al 2010) were suggested by Hill et al (2011) because of similarities of the optical spectra (both sources were formerly proposed as CVs), the existence of radio and Fermi-LAT counterparts and the short, putative ∼4 h orbital period, and large optical flickering. PSR J1023+0038 was proposed to be active in gamma rays when accretion switches off and evidence of accretion stopping at least once comes from an optical, although non-simultaneous, spectrum (see Tam et al 2010 and reference therein).…”
Section: An Lmxb Hosting An Msp?mentioning
confidence: 91%
See 1 more Smart Citation
“…The pulsar wind electrons and positrons are accelerated and randomized by the shock and emit the X-rays via the synchrotron process. Such shock emission has also been suggested to explain the variable X-ray flux as a function of orbital phase in 47 Tuc W (Bogdanov et al 2005) and PSR J1740-5340 in NGC 6397 (Huang & Becker 2010) and PSR J1023+0038 (Archibald et al 2009(Archibald et al , 2010Tam et al 2010;Bogdanov et al 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Their presence, including the transitional properties for two redbacks PSR J1023+0038 [4] and XSS J12270−4859 [6], challenges our understanding for the formation process of MSPs (e.g., [8,7]). It is warranted to find more of them among Fermi sources, particularly given that PSR J1023+0038 and XSS J12270−4859 have detectable γ-ray emission and showed related flux changes when they had state transitions [23,19,11,28]. It is extremely difficult to find millisecond pulsation signals in Fermi LAT data via blind searches [14].…”
Section: Msp Modulation Estimatesmentioning
confidence: 99%